Plant branching habits, seed maturity stages and drying effects on seed quality of Dukung Anak (Phyllanthus amarus Schum. & Thonn. and Phyllanthus debilis Klein ex Willd) - Abdurahman, Sharif Azmi (2018)
Dukung Anak is a well-known herb due to its medicinal value. Realizing the potential, Malaysian government through National Key Economic Areas (NKEA) has extensively promoted the cultivation of this herb to boost the economy. Phyllanthus amarus and Phyllanthus debilis are two of the commercially grown species in Malaysia. However, the availability of good quality seeds as planting material is limited resulting in poor quality (< 50% germination) and erratic germination. Current method of collecting dehisced seeds may be improved by harvesting matured seeds prior to dehiscence and subjecting them to desiccation. Therefore, three studies were carried out; plant branching habits in relation to fruit production, differences in seed quality at different maturity stages and drying effects on seed quality of P. amarus and P. debilis. In the first study, plants were grown using standard cultural practises, in which plant growth and development event was observed and studied and plant architecture model was developed. Both P. amarus and P. debilis had main stem with monopodial while branches being plagiotropic with sympodial growth. Fruits were formed on branchlets from main stem as well as primary branches. Substantial number of fruits were obtained from 56 to 98 days after sowing (DAS) for P. amarus and 63 to 105 DAS for P. debilis. In the second study, fruits and seeds were collected at different maturity stages (7, 9, 11, 13, 15 days after anthesis (DAA) and dehisced seeds for P. amarus and 7, 9, 11, 13 DAA and dehisced seeds for P. debilis) and from different branchlets on main stem and primary branches. Seed moisture content and seed germination test was carried out to know the viability and vigour of the seeds. Fruits and seeds collected from different position showed no effects on seed quality but it was significantly affected by the level of maturity stages. Maximum dry weight was observed 13 DAA for P. amarus (43.74 mg/100 seeds) and 11 DAA for P. debilis (73.56 mg/ 100 seeds) indicating PM with germination at PM of 74%, and 69% respectively. However, moisture content was high at 35% for P. amarus and 33% for P. debilis. However, best quality seed was obtained during dehiscence with a moisture content of 15% and germination of 95% (P. amarus) and 92% (P. debilis). In the third study, fresh seeds of different maturity stages were immediately dried using two different methods, under rain shelter and in air-conditioned room for three days before seed moisture content and germination test. Both methods managed to reduced seed moisture content to less than 15% for all maturity stages. Seed quality during PM was improved to 89% (P. amarus) and 79% (P. debilis) after drying under rain shelter condition for three days. In conclusion, seeds can be collected prior to dehiscence as early as 13 DAA and 11 DAA for P. amarus and P. debilis and dried under rain shelter for three days to obtain seed quality similar to that at dehiscence. For seed collection, fruits can be harvested from 56 to 98 DAS for P. amarus and 63 to 105 DAS for P. debilis.